Current efforts in research of pleural mesothelioma—An analysis of the ClinicalTrials.gov registry. (October 2018) - Süveg, Krisztian; Putora, Paul Martin; Berghmans, Thierry; Glatzer, Markus; Kovac, Veljko; Cihoric, Nikola
Highlights: Recent guidelines from the ASCO and the BTS demonstrate significant discrepancies. Ongoing trials in MPM are mostly in early phases and dominated by systemic therapies. Very few trials evaluate loco-regional therapeutic approaches. Current controversy surrounding local therapies will not be answered in the next years. Abstract: Objectives: Currently there are many uncertainties in the optimal treatment of malignant pleural mesothelioma (MPM), this is reflected in discrepancies between current guidelines. Our aim was to evaluate the current status of prospective interventional clinical trials within the ClinicalTrials.gov registry in MPM in order to predict a potential impact on MPM management in the next years. Material and Methods: The records of 263.832 clinical trials registered were searched in December 2017. Trials starting between 2005 and 2017 (n = 262) were selected for further manual review. Trials including other tumour entities or mesothelioma originating outside the pleura (n = 94) were excluded, as well as trials where the primary endpoint has already been published (n = 22). Results: In total, 91 clinical trials were identified and selected for further analysis. Most trials had a single arm design, were in phase I, and were non-randomized. Academic centres were recorded as primary sponsors in the majority of trials (56%), followed by industry in 21%. Most studies investigated targeted (n = 42) or cytotoxic therapies (n = 39). Ten studies investigated different genetic therapies. In 67% of the trials (n = 61) targeted and/or cytotoxic therapies were involved. Treatments involving surgery were investigated in 12 trials (13%), radiotherapy in 10 trials (11%). Only five studies (6%) were phase 3 studies and one was a phase 2/3 study. Four of these five phase 3 trials investigated targeted therapies, while one trial investigated prophylactic radiotherapy of operative tracts. Conclusions: Currently running trials in MPM are mostly in early phases and dominated by systemic therapies. Very few trials evaluate loco-regional therapeutic approaches. The current controversy surrounding the use of surgery and radiotherapy within multimodal therapy strategies will not be answered by these trials in the coming years.